Decompression Retinopathy Following Trabeculectomy: A Case Report - Rishi, Ekta; Sood, Gitanjli; Khurana, Mona; Rishi, Pukhraj (Nepalese Journal of Ophthalmology, 2020)
Introduction: Decompression retinopathy (DR) can have varied manifestations as retinal and vitreous hemorrhage, disc edema, and macular edema. Vein occlusion associated with choroidal detachment (CD) has not been reported so far as a feature of DR. Case: We report a case of a 78 year old male with bilateral primary open angle glaucoma (POAG) on maximal topical medication with progressive field loss. Trabeculectomy with mitomycin C was done in the left eye, and the patient developed hypotony in the immediate postoperative period which was managed conservatively. After six weeks he developed CD, vein occlusion and macular edema. Thus, Anti VEGF was given and in other eye filtration surgery was done with all measures to avoid sudden hypotony. Patient still developed CD in the right eye. For which, he was given oral and topical steroids in tapering dose. After one month there was resolution of macular edema in the left eye and choroidal detachment resolved in both eyes and IOP was in lower teens in both eyes. Conclusion: Venous stasis retinopathy and choroidal detachment can be the manifestations of decompression retinopathy following glaucoma filtering surgery. The advancement in imaging modalities now can help us find the pathogenesis of the condition and validation of previous hypothesis proposed. Early identification and management of retinopathy helps in resolution with good visual recovery.